Fine Mapping and Candidate Gene Analysis of Resistance Gene RSC3Q to Soybean mosaic virus in Qihuang 1 - Gui-jie ZHENG; Yong-qing YANG; Ying MA; Xiao-feng YANG; Shan-yu CHEN; Rui REN; Da-gang WANG; Zhong-lu YANG; Hai-jian ZHI (Journal of Integrative Agriculture)
Soybean mosaic virus (SMV) disease is one of the most destructive viral diseases in soybean (Glycine max (L.) Merr.). SMV strain SC3 is the major prevalent strain in Huang-Huai and Yangtze valleys, China. The soybean cultivar Qihuang 1 is of a rich resistance spectrum and has a wide range of application in breeding programs in China. In this study, F1, F2 and F2:3 from Qihuang 1×Nannong 1138-2 were used to study inheritance and linkage mapping of the SC3 resistance gene in Qihuang 1. The secondary F2 population and near isogenic lines (NILs) derived from residual heterozygous lines (RHLs) of Qihuang 1×Nannong 1138-2 were separatively used in the fine mapping and candidate gene analysis of the resistance gene. Results indicated that a single dominant gene (designated RSC3Q) controls resistance, which was located on chromosome 13. Two genomic-simple sequence repeat (SSR) markers BARCSOYSSR_13_1114 and BARCSOYSSR_13_1136 were found flanking the two sides of the RSC3Q. The interval between the two markers was 651 kb. Quantitative real-time PCR analysis of the candidate genes showed that five genes (Glyma13g25730, 25750, 25950, 25970 and 26000) were likely involved in soybean SMV resistance. These results would have utility in cloning of RSC3Q resistance candidate gene and marker-assisted selection (MAS) in resistance breeding to SMV.